Influence of Ohmic heating on the Proximate Composition and Consumer Acceptability Scores of African Breadfruit Seed Flour (e-Proceedings of the Faculty of Agriculture International Conference, 2023)
This work compared the effect of Ohmic heating (115V, 100°C) using aluminum electrodes and some sodium salts with conventional heating as a possible heat source for parboiling operation as it affects the nutritional quality of the dehulled African breadfruit seeds. The protein content ranged from 15.75-19.60%, fat content ranged from 5.97-7.54%, starch content ranged from 1.6-2.9 mg/ml while samples Ohmic heated with sodium chloride had the highest overall consumer acceptability score of 8.3 (on a 9-point hedonic scale), thus adjudged the best in this study.
Keywords: African breadfruit; Aluminium electrodes; Dehulling; Ohmic heating; Parboiling